Using graphene multilayers to transform the performance and functionality of atom chips for use in quantum sensors - Crawford, Rosemary (2019)
Current atom chips, conventionally made from metal wires, suffer from anumber of different problems, which we have shown can be overcome byusing graphene conductors, specifically;